Civil society: theoretical and methodological approaches and international studies on Kazakhstan - Muratova, M.M.; Onuchko, М.Ю. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
The article provides an overview of the main studies on the state of development of civil society in Kazakhstan, carried out by international organizations. At the same time, the authors analyzed the main theoretical and methodological approaches to the study of civil society and its place, and the role in the consolidation and stability of public relations and considered various definitions of the concept of civil society, their features, and differences. The methodology used in this article is based on a qualitative method - the analysis of documents presented as a set of questions to the text, to which the researcher answers during the analysis of the text of the document. The source base of the study was country profiles, studies in the field of civil society in Kazakhstan, published after 2010. Based on the review, the article identifies the main barriers to the development of the civil sector in Kazakhstan, which is represented by the weak financial stability of organizations, the presence of the sector’s dependence on the state and donors, weak interaction of the civil sector organizations with the media, and a low level of involvement of the population in the activities of civil society institutions. In addition, the strengths and points of possible growth are highlighted. The scientific significance of the article lies in the increment of knowledge about the current state and development of civil society in Kazakhstan. The practical significance is determined by the possibility of the practical application of the main findings of the study. Based on the analysis, the authors determined that research on the development of the civil sector in Kazakhstan is characterized by the prevalence of research in the NGO sector when such institutions as trade unions, charitable foundations, political parties (from the standpoint of the development of civil society) have been little studied.